Management of Hasta bahar in Acid Lime cv. Kagzi (Indian Journal of Arid Horticulture, 2025)
A field experiment was conducted on acid lime cv. Kagzi for management of Hasta bahar with 15 treatments comprising of chemicals applied through foliar spray viz., GA, (50 and 75 ppm), NAA (400 & 500 ppm, KNO, (1 & 1.5%), Cycocel (1000 & 1500 ppm), PP, (1000 & 2000 ppm), applied through soil drenching viz., PP,,, (2.5 & 5 ml plant'), cultural practices (Root pruning + exposure and withholding of irrigation water) and control. Cycocel @1000 ppm in the month of September gave early induction of flowering (2, November), maximum number of flowers shoot' (60.0), fruit set (19.50%), highest fruit retention (49.0%), maximum number of fruits tree' (634), highest yield tree' (30.50 kg) and yield ha" (8.47 t) and best quality parameters such as high ascorbic acid (39.20 mg 100ml juice), juice per cent (52.78), organoleptic score (8.95) with higher B:C ratio (3.46).
Keywords: Hasta bahar; Acid lime; PGRS; Crop regulation